Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To solve for the value of \( p \) in the quadratic equation \( px^2 - x + 1 = 0 \), given that the sum of its zeroes (or roots) is -2, follow these steps:
1. Identify the properties of a quadratic equation:
For a quadratic equation of the form \( ax^2 + bx + c = 0 \), the sum of its roots \( (\alpha + \beta) \) is given by the formula:
[tex]\[ \alpha + \beta = -\frac{b}{a} \][/tex]
2. Substitute the coefficients:
In our given quadratic equation \( px^2 - x + 1 = 0 \), it's clear that:
[tex]\[ a = p, \quad b = -1, \quad \text{and} \quad c = 1 \][/tex]
3. Apply the sum of the roots formula:
According to the formula for the sum of the roots:
[tex]\[ \alpha + \beta = -\frac{b}{a} \][/tex]
Substituting the values of \( b \) and \( a \):
[tex]\[ \alpha + \beta = -\frac{-1}{p} = \frac{1}{p} \][/tex]
4. Use the given sum of the zeroes:
We are given that the sum of the zeroes is -2:
[tex]\[ \frac{1}{p} = -2 \][/tex]
5. Solve for \( p \):
To isolate \( p \), we solve the equation:
[tex]\[ \frac{1}{p} = -2 \implies p = -\frac{1}{2} \][/tex]
Hence, the value of \( p \) is:
[tex]\[ p = -0.5 \][/tex]
1. Identify the properties of a quadratic equation:
For a quadratic equation of the form \( ax^2 + bx + c = 0 \), the sum of its roots \( (\alpha + \beta) \) is given by the formula:
[tex]\[ \alpha + \beta = -\frac{b}{a} \][/tex]
2. Substitute the coefficients:
In our given quadratic equation \( px^2 - x + 1 = 0 \), it's clear that:
[tex]\[ a = p, \quad b = -1, \quad \text{and} \quad c = 1 \][/tex]
3. Apply the sum of the roots formula:
According to the formula for the sum of the roots:
[tex]\[ \alpha + \beta = -\frac{b}{a} \][/tex]
Substituting the values of \( b \) and \( a \):
[tex]\[ \alpha + \beta = -\frac{-1}{p} = \frac{1}{p} \][/tex]
4. Use the given sum of the zeroes:
We are given that the sum of the zeroes is -2:
[tex]\[ \frac{1}{p} = -2 \][/tex]
5. Solve for \( p \):
To isolate \( p \), we solve the equation:
[tex]\[ \frac{1}{p} = -2 \implies p = -\frac{1}{2} \][/tex]
Hence, the value of \( p \) is:
[tex]\[ p = -0.5 \][/tex]
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.